Legalitas SK Pegawai Negeri Sipil Yang Dijadikan Jaminan Kredit Perbankan - Maulana Falah Akbar; Endang Prasetyawati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The primary function is to provide credit to financial institutions, since this is where the majority of a bank's revenue (interest, fees, and other forms of income) is generated. How profitable and long lasting a bank is depends on the quantity of credit that is extended. Consequently, every step of the lending process from estimating the amount of credit to calculating interest rates, from issuing credit to analyzing it, and finally, from returning poor credit must be executed to the highest standard. On the other hand, lending is a crucial part of a bank's strategy, and it's also a common reason why banks go bankrupt. What is the intended outcome of this study? 1) Under what circumstances may creditors accept a Civil Servant Decree (SK) as security? 2) How would the bank, as the creditor, handle a dispute in the event of a legal dispute (poor credit)? 3) Who is legally responsible for a banker's clients' negative credit? Research in this area follows a juridical-normative framework. A judicial-normative strategy is one that looks at information from the web, books, and relevant legislation.